Hydroxychloroquine and lupus pregnancy: review of a series of 36 cases. Issue 7 (July 1996) - Buchanan, N M; Toubi, E; Khamashta, M A; Lima, F; Kerslake, S; Hughes, G R
Abstract : OBJECTIVE: To study maternal and fetal outcome of pregnancy in patients with lupus who were exposed to hydroxychloroquine (HCQ). METHODS: The case records of women (n = 33) exposed to HCQ during their pregnancies (n = 36) and of 53 control patients from a single lupus pregnancy centre were reviewed to determine lupus activity, obstetric experience, and infant outcome. RESULTS: HCQ was not apparently teratogenic. Lupus activity and obstetric outcome in the two groups were similar. CONCLUSION: HCQ continuation is probably safe during pregnancy in patients with lupus, but there is no obvious advantage in commencing treatment.